2017
DOI: 10.3389/fmicb.2017.00613
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation and Lytic Replication of Kaposi’s Sarcoma-Associated Herpesvirus: An Update

Abstract: The life cycle of Kaposi’s sarcoma-associated herpesvirus (KSHV) consists of two phases, latent and lytic. The virus establishes latency as a strategy for avoiding host immune surveillance and fusing symbiotically with the host for lifetime persistent infection. However, latency can be disrupted and KSHV is reactivated for entry into the lytic replication. Viral lytic replication is crucial for efficient dissemination from its long-term reservoir to the sites of disease and for the spread of the virus to new h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(159 citation statements)
references
References 241 publications
(306 reference statements)
1
158
0
Order By: Relevance
“…Physiological triggers that induce gammaherpesvirus reactivation are not as clear as in the case of other herpesviruses (see below). Infections by other viruses, such as HIV, HSV-1, HSV-2, HHV-6, HHV-7, HCMV, and papillomavirus can contribute to lytic reactivation of KSHV [179][180][181][182]. Further research has shown that activation of Toll-like receptors 6 and 7 (TLR6 and TLR7) by other viruses can trigger KSHV reactivation [180].…”
Section: Virus Reactivationmentioning
confidence: 99%
“…Physiological triggers that induce gammaherpesvirus reactivation are not as clear as in the case of other herpesviruses (see below). Infections by other viruses, such as HIV, HSV-1, HSV-2, HHV-6, HHV-7, HCMV, and papillomavirus can contribute to lytic reactivation of KSHV [179][180][181][182]. Further research has shown that activation of Toll-like receptors 6 and 7 (TLR6 and TLR7) by other viruses can trigger KSHV reactivation [180].…”
Section: Virus Reactivationmentioning
confidence: 99%
“…A classic example is herpes simplex virus-1 (HSV-1/HHV- 1) infection, which produces primary vesicular lesions in the oral mucosa and establishes latency in adjacent neural ganglia where reactivation of the virus leads to formation of repeated lesions in the same area over the course of the infected individual's life [4][5][6]. Other herpesviruses such as human cytomegalovirus (HCMV/HHV-5) and Kaposi's sarcoma-associated herpesvirus (KSHV/HHV-8) establish latency in various myeloid and lymphoid compartments, often without symptoms associated with reactivation except in the cases of immunosuppression such as organ transplantation or untreated HIV-1 infection [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, tumors associated with KSHV infection mostly present with viruses in a latent state; this observation led to the consideration of lytic reactivation not involved in tumorigenesis. Actually, it is recently emerging that both latency and lytic reactivation play a key role in KSHV-induced carcinogenesis (Aneja and Yuan, 2017). To this regard, it has been characterized that latent infection promotes proliferation and cell survival (Cesarman et al, 2019); by counterpart, virus reactivation not only ensures a higher dissemination of viral particles but also promotes angiogenesis (Asou et al, 1998;Wu et al, 2014) and the evasion of immunoresponse (Zhao et al, 2015), promoting cancer development.…”
Section: Kaposi's Sarcoma-associated Herpesvirus (Kshv)mentioning
confidence: 99%